CT clot characteristics and success of endovascular thrombectomy in acute anterior circulation ischemic stroke - Naphon; Lertutsahakul, Krittanon; Jakchairoongruang, Ketsuda (The ASEAN Journal of Radiology, 2025)
Background: CT and CT angiography (CTA) have been informative for acute occlusive thrombus. Conflicting results of the thrombus characteristics and endovascular thrombectomy (EVT) revascularization outcome have been debated. Objective: We aimed to evaluate CT clot characteristics and EVT outcomes in acute ischemic stroke patients. Materials and Methods: Unenhanced CT and multiphase CTA brain of 59 acute anterior-circulation ischemic stroke patients undergoing EVT from November 2019 to June 2021 were reviewed. The following clot characteristics were assessed: the most proximal clot location, clot length, clot burden score (CBS), distance from the terminal ICA to the most proximal part of the clot (DT), clot heterogeneity, mean clot attenuation, relative mean clot attenuation to contralateral artery, and clot perviousness. The standard deviation (SD) of the measured clot attenuation represented clot heterogeneity. At least mTICI 2b on post-thrombectomy cerebral angiography was considered successful revascularization. Descriptive and analytic statistical analyses were obtained with p<0.05 considered significant. Results: Fifty two of 59 cases (88.1%) had successful thrombectomy. DT was significantly shorter in the successful group (8.5±9.1 mm) versus the unsuccessful group (16.4±13.2 mm) with p=0.046; however, association between DT and revascularization outcomes did not reach statistical significance (OR=0.94; 95%CI=0.87-1.00; p=0.061). Clot heterogeneity and other characteristics showed no differences between two groups or associations with outcomes. Conclusion: Among the clot features on unenhanced CT and multi-phase CTA brain in our study group, distance of the clot from terminal ICA (DT) was significantly shorter in the successful EVT group. Further assessment of clot characteristics and EVT outcome in larger numbers of cases should be sought for a potential predictor of success.